Heritage interpretation assessment framework for historic house museums in Singapore: A case study of the NUS baba house - Zijie, Zhou (Institute for Advanced Science Social, and Sustainable Future, 2024)
Singapore is increasingly preserving historically significant structures through adaptive reuse, notably using historic house museums to connect with local history. NUS Baba House, a well-preserved Peranakan townhouse, is a prime example of this. Evaluating heritage interpretation at NUS Baba House can clarify relevant criteria, but existing principles lack specificity for the heritage interpretation of Singaporean historic house museums. This paper systematically assesses NUS Baba House's heritage interpretation using a literature-based framework, providing tailored recommendations across five dimensions: authenticity, sustainability, professionalism, guided tour interactivity, inclusiveness, and community engagement. While further validation through case studies is needed, this study offers a practical framework to enhance heritage interpretation at Singaporean historic house museums, filling a gap in current guidelines.